PERAN GANDA PEREMPUAN DALAM MENYEIMBANGKAN KARIER DAN KELUARGA - Aulia Putri, Rasikha; Rahmayanty, Dinny (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2023)
Modern women are faced with the dual role of being a homemaker and a careerist. This can be a big challenge, as both roles are equally important and require a high level of dedication and bring various challenges in balancing work and family responsibilities. Women's dual role in balancing career and family is one of the important cornerstones in creating balanced well-being. Women who work and have a role as housewives must manage their time and energy well to ensure family welfare and increase family income. This article discusses the dual role of women and the strategies that can be applied to achieve a balance between career and family